The pattern of peritoneal colorectal metastasis predicts survival after cytoreductive surgery and hyperthermic intra-peritoneal chemotherapy. Issue 1 (January 2022) - Assaf, Dan; Mor, Eyal; Laks, Shachar; Zohar, Nitzan; Benvenisti, Haggai; Hazzan, David; Segev, Lior; Akopyan, Olga Klebanov; Shacham-Shmueli, Einat; Margalit, Ofer; Halpern, Naama; Boursi, Ben; et al.
Abstract: Background: Peritoneal cancer index (PCI) has been used reliably to prognosticate patients with peritoneal metastasis, however, it fails to describe the patterns of peritoneal spread and to correlate these patterns to survival outcomes. We aim to define the scattered peritoneal spread (SPS) as a pattern associated with worse survival in colorectal peritoneal metastasis. Methods: A retrospective analysis of metastatic colorectal cancer patients from a prospectively maintained database of peritoneal surface malignances ( n = 280) between 2015 and 2020. SPS was defined by the presence of at least two distant and non-contiguous PCI regions. We compared patients with SPS ( n = 73) and clustered peritoneal spread (CPS) ( n = 88) for demographics, perioperative and survival outcomes. Results: No difference in demographics or post-operative course was noted between the groups. The median follow-up was 15.4 months (0.4–70.8 months). Worse disease-free survival (DFS) in the SPS group with an estimated median of 8.2 months compared to 22.5 months in the CPS spread group, ( p = 0.001). The estimated median overall survival (OS) for SPS group was 35.7 months whereas in the CPS group the median was not reached ( p = 0.025). The same effect of SPS was preserved even after stratification of PCI. Conclusions: We defined and described the association of the peritoneal spread pattern to survival outcomes. SPS patients exhibit worse DFS and OS independent of the PCI level. Integration of malignant spread pattern into prognostication models along with PCI may aid in predicting oncological outcomes. Abstract : Synopsis: The scattered pattern of peritoneal metastasis from colorectal malignancy predicts worse prognosis after cytoreductive surgery and hyperthermic intra-peritoneal chemotherapy.